Understanding the cooperative atomic motion and shape change of ultrasmall Au nanoparticles below the premelting temperature. Issue 88 (8th December 2017) - Yang, Ying; Yan, Ning
Abstract : Surface melting is widely observed in crystalline materials, which has a significant influence on their interfacial properties. Abstract : Surface melting is widely observed in crystalline materials, which has a significant influence on their interfacial properties. In this computational study using molecular dynamics simulations, we observed that at 50 K below the onset temperature of surface melting, the "out-shell" atoms of ultrasmall Au nanoparticles (NPs) have already undergone remarkable rearrangements. Unlike the observations in Ni ultrasmall NPs, the resulting shape change was often isotropic. Further investigations reveal that such interfacial motions are cooperative and string-like. The gold "atom strings" do not migrate through the center of the particle, behaving similarly as those in much larger particles. Therefore, the "spherical" shape was sustained during the atomic motions. This result reveals the dynamic nature of the atomic motions of Au before the commencement of premelting and sheds light on the understanding of the origin of surface melting.